(3QSGdI aj GdYed HGdQHY GdebfWQIs - (3bQg MUGQj, CMeO fjGRj Hf MSfs
(3ChdgG (B:s
(3GdMeO ddg gPg QSGdI NJUQI aj GdYd HGdQHY GdebfWQI eTJedI Ydi ebOeI hSHYI CHhGH GdebOeI aj GdQShe GdeQcR gh GdeNQL ebOeg HJSYjf GdNW GdeTQb hGdeZQH gh GdNW GdCjefs
(3BNQgG (B:s
(3eKdG EPG cGf hbJ GdEeSGc YTQI SGYI hSJI YTQ ObjbI aCNQL gPg GdObjbI aHbj YTQI SGYI ajchf hbJg YTQI SGYI hKeGfjI ObjbI HdG JbOe hdG JCNQ HGdSGYI Jes
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3Gdadc hGdJfLje hGdejbGJs